Olfaction and Executive Cognitive Performance: A Systematic Review - Challakere Ramaswamy, Vasudeva Murthy; Schofield, Peter William (Frontiers in Psychology, 2022)
Objective tests of olfaction are widely available to aid in the assessment of olfaction. Their clearest role is in the characterization of olfactory changes, either reported by or suspected in a patient. There is a rapidly growing literature concerned with the association of olfactory changes with certain neuropsychiatric conditions and the use of olfactory testing to supplement conventional assessments in clinical and research practice is evolving. Neural pathways important for olfactory processing overlap extensively with pathways important for cognitive functioning, and especially those important for executive functioning, many of which are concentrated in the frontal lobes. Previous work has identified associations between performance on certain olfactory tests (most frequently olfactory identification) and executive functioning and behavioral measures (e.g. of impulsivity). More recently, similar associations have also been identified in non-clinical samples, raising new questions as to the utility of olfactory test scores as proxy measures for non-olfactory phenomena. In this systemic review, we sought to identify studies, both clinical and non-clinical, that investigated the associations of olfaction with performance on tasks sensitive to frontal lobe functioning. Our search criteria led to the identification of 70 studies published in English. We examined in detail and tabulated the data from these studies, highlighted each study's key findings, and critically evaluated these studies. We use the results of this review to reflect on some of the current and future challenges concerning the use of olfactory testing in clinical neuropsychiatric practice and research and speculate on the potential benefits of administering phonemic fluency in combination with olfactory testing to enhance its predictive value.